1997
DOI: 10.1159/000112998
|View full text |Cite
|
Sign up to set email alerts
|

Cyto- and Myeloarchitectonic Organisation of the Spinal Cord of an Echidna (Tachyglossus aculeatus)

Abstract: We have studied the cyto- and myeloarchitectural organisation of the spinal cord of an echidna (Tachyglossus aculeatus) with the aid of Nissl staining, darkfield examination and p-phenylenediamine staining. We have also examined the distribution of unmyelinated afferents by labelling with a peroxidase-conjugated lectin derived from Griffonia simplicifolia (B4 isolectin). The cytoarchitectural features characterising the laminar organisation of the spinal cord in eutherian mammals were broadly applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…The results of this study confirm previous reports of BSI-B 4 binding in the rat, mouse, and rabbit (Streit et al, 1985;Kruger, 1988, 1990;Plenderleith et al, 1992;Plenderleith and Snow, 1993;Kitchener et al, 1994;Wang et al, 1994), and are entirely consistent with studies reporting BSI-B 4 binding in dorsal root ganglia and spinal cord of the chicken (Scott et al, 1990), echidna (Ashwell and Zhang, 1997), opossum (Knott et al, 1999), and rhesus monkey (Tong et al, 1999). Furthermore, recent studies have reported BSI-B 4 binding sites on human primary sensory neurones collected either post-mortem or from patients undergoing surgery (Yiangou et al, 2000;Alavi et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study confirm previous reports of BSI-B 4 binding in the rat, mouse, and rabbit (Streit et al, 1985;Kruger, 1988, 1990;Plenderleith et al, 1992;Plenderleith and Snow, 1993;Kitchener et al, 1994;Wang et al, 1994), and are entirely consistent with studies reporting BSI-B 4 binding in dorsal root ganglia and spinal cord of the chicken (Scott et al, 1990), echidna (Ashwell and Zhang, 1997), opossum (Knott et al, 1999), and rhesus monkey (Tong et al, 1999). Furthermore, recent studies have reported BSI-B 4 binding sites on human primary sensory neurones collected either post-mortem or from patients undergoing surgery (Yiangou et al, 2000;Alavi et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to the discontinuous distribution of CB immunoreactivity seen in the Sp5C of the echidna and suggests that at least the unmyelinated C fibre afferents are irregularly distributed in the caudal parts of the Sp5 of the echidna. Our study of the echidna spinal cord (Ashwell and Zhang, 1997) showed a similar distribution of lectin labelled afferents in patches deep within the dorsal horn rather than being confined to the gelatinosus layer of the dorsal horn as described for rodents (Plenderleith et al, 1989). This anatomical difference may point to dissimilarities between the echidna and rodents in the processing of information carried by C fibres at both the trigeminal and spinal cord level, but further study would be necessary to confirm this.…”
Section: Lectin Histochemistry Of Trigeminal Afferents In Monotremes supporting
confidence: 78%
“…In the brainstem of rodents, this lectin gives terminallike staining in the inner part of lamina II of Sp5C, binding unmyelinated C-fibre primary afferents (Ambalavanar and Morris, 1993). We have previously used this lectin in our study of unmyelinated afferents to the spinal cord of the echidna (Ashwell and Zhang, 1997) and showed that this lectin labels small unmyelinated primary afferents (presumably comprising the C type fibres) arising from small ganglion cells, similar to that seen in rodents (Streit et al, 1985;Plenderleith et al, 1989).…”
Section: Lectin Histochemistry Of Trigeminal Afferents In Monotremes mentioning
confidence: 67%
See 2 more Smart Citations